Quality assessment of medical records at Clinica Centenario Peruano Japonesa internal medicine doctor’s offices, 2010 – 2011 - Matzumura Kasano, Juan P. (2014)
Core of medical audit is a properly tailored medical history. The medical record includes all medical examinations, studies conducted and treatments applied during the course of the disease. Objectives: To assess medical records registration quality of Internal Medicine doctor’s offices at Clinica Centenario Peruano Japonesa. Design: Descriptive cross-sectional study. Location: Internal Medicine outpatient offices at Clinica Centenario Peruano Japonesa. Material: Clinical records of patients attended in Internal Medicine doctor’s offices. Methods: Three hundred and twenty-three medical records were collected by random sampling and subjected to a 10-items record audit, each rated at 10 points, for a total of 100 points. Items included date and time of care, neatness and legibility suitable record, vital signs, physical examination, diagnosis, plan of work, laboratory findings, complete treatment, and signature and stamp of the physician. Records with total score more than or equal to 80 were rated as ‘acceptable’, and all others as ‘need to improve’. Main outcome measures: ‘Acceptable’ or ‘need to improve’ medical records. Results: Two hundred and six (63.8%) clinical records were rated as ‘acceptable’ and 117 (36.2%) as ‘need to improve’. Items diagnosis and complete treatment presented poor registry more frequently, both in records with acceptable registry (filled in completely in 64.6% and 62.6% respectively) and those with need to improve registry (20.5% and 23.1% respectively). Signature and seal of the attending physician were the best items in both categories (99.5% and 93.2% respectively). Conclusions: More than half of the medical records had an acceptable quality at the Clinica Centenario Peruano Japonesa.